Exclusions of the Public Sphere Conception: Examining Deliberative and Discourse Theory Accounts - Dahlberg, Lincoln (Javnost-The Public, 2013)
The deliberative conception of the public sphere has proven popular in the critical evaluation of the democratic role of media and communication. However, the conception has come under sustained critique from poststructuralist- influenced theorists, amongst others, for failing to fully account for the exclusions that result from it being defined as a universal norm of public sphere deliberation. This paper examines how this critique may be answered. It does so first by exploring how (sophisticated) deliberative theory can reply to the critique, and second by turning to the poststructuralist-influenced critics – specifically post-Marxist discourse theorists – and asking how they might provide a way forward. With respect to the first, the paper finds that deliberative theory can, and often does, account for the exclusions in question much more than critics suggest, but that there remains concern about the conception’s radical democratic status given that exponents (seem to) derive it extra-politically. With respect to the second, the paper finds that a post-Marxist discourse theory reading – that embraces radical contingency – of the deliberative public sphere conception provides a purely political framework for theorising deliberative exclusion (and associated politics), and thus offers an ontological and democratic radicalisation of the public sphere conception. However, given the embrace of radical contingency, and thus acceptance of inelminable power, the paper concludes by indicating that this radicalisation may illicit concern about its radical democratic status.